If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(-1) = 25x + -5x Reorder the terms for easier multiplication: -1f = 25x + -5x Combine like terms: 25x + -5x = 20x -1f = 20x Solving -1f = 20x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '-1'. f = -20x Simplifying f = -20x
| 5x+15=28x | | (17w-13)+(-6w+7)= | | .28x=700 | | x=-1.25y+3 | | 4.1x-17.49=2.6 | | (7w-13)+(-6w-7)= | | x-3=-1.25y | | f(-1)=4x-2x | | t+8t= | | f(2)=16x-2x | | 6x^2-84x+160=0 | | Y=-0.6(3)+0 | | 3sin^2x-3sinx-2=0 | | K+8=6(k-11) | | 14-2x=20-5x | | (10a+7)(3a-4)=0 | | 3y+15x=6 | | -8a+3a=15 | | 99=(w+2)(w) | | 6p-10q= | | f(-1)=16x-2x | | 5n-3=-188 | | 2b-3.4=-1.74 | | 121/8+f=194/5 | | c=50i^2+2000 | | f(0)=16x-2x | | 7(6-x)=-28 | | 6x^2-2x^2-2=-9x+1 | | 3.6=6.4-0.7X | | 8x-8=-136 | | 0=cos(4x) | | (fx)=4 |